2018
DOI: 10.1177/1556264618783555
|View full text |Cite
|
Sign up to set email alerts
|

When Nursing Care and Clinical Trials Coincide: A Qualitative Study of the Views of Nordic Oncology and Hematology Nurses on Ethical Work Challenges

Abstract: This study investigated the kinds of ethical challenges experienced by nurses in oncology and hematology when nursing care and research overlap in clinical trials, and how the nurses handle such challenges. Individual interviews with 39 nurses from Sweden, Denmark, and Finland indicated that all nurses were positive about research, considering it essential for developing the best care. Ethical challenges exist, however; the most difficult were associated with the end-of-life patients, no longer responsive to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 28 publications
0
28
2
Order By: Relevance
“…While role conflicts can occur at any time during a study, they appear strongly during the informed consent process (Cantini & Ells, ; Cresswell & Gilmour, ; Godskesen et al, ; Hill & MacArthur, ; Höglund et al, ). Research nurses’ role conflicts and ethical dilemmas within the informed consent process include being asked to approach patients about a study at an inappropriate time, patients not reading the consent form due to their trust of healthcare professionals and patients not being fully informed of what is required in the study (Cantini & Ells, ).…”
Section: Discussionmentioning
confidence: 99%
“…While role conflicts can occur at any time during a study, they appear strongly during the informed consent process (Cantini & Ells, ; Cresswell & Gilmour, ; Godskesen et al, ; Hill & MacArthur, ; Höglund et al, ). Research nurses’ role conflicts and ethical dilemmas within the informed consent process include being asked to approach patients about a study at an inappropriate time, patients not reading the consent form due to their trust of healthcare professionals and patients not being fully informed of what is required in the study (Cantini & Ells, ).…”
Section: Discussionmentioning
confidence: 99%
“…Considering stroke survivors' medical condition and vulnerability, it might be challenging to take a neutral or distant attitude towards the participant. However, data collectors are confronted with the demand to balance the ethical challenges that might arise when opposing ethical obligations to care and research overlap (40).…”
Section: The Data Collectorsmentioning
confidence: 99%
“…Part I is empirical and consists of semi-structured interviews, while Part II comprises a literature review to provide a comprehensive summary of current evidence relevant to the question of whether clinical trials are superior to standard care. The empirical data were collected as part of a larger project (briefly summarised below) that is described in detail elsewhere, including recruitment and data collection [15,16]. We followed the Standards for Reporting Qualitative Research (SRQR) in methods, results and discussion to improve the quality and transparency [26].…”
Section: Designmentioning
confidence: 99%
“…Peppercorn et al [14] cited several typical examples of oncologists who believe that patients in trials have better outcomes than those not in a trial. In previous studies we found that this is an important issue for physicians and nurses who experience ethical challenges when clinical care and research are intertwined [15,16]. Physicians and nurses found that a most difficult challenge was end-of-life patients eager to participate in all kinds of cutting-edge drug trials, often with an unrealistic hope for possible gain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation